1990
DOI: 10.1037/0022-3514.59.5.941
|View full text |Cite
|
Sign up to set email alerts
|

Gender, language, and influence.

Abstract: College of the Holy Cross Mixed-and same-sex dyads were observed to examine effects of gender composition on language and of language on gender differences in influence. Ss discussed a topic on which they disagreed. Women were more tentative than men, but only in mixed-sex dyads. Women who spoke tentatively were more influential with men and less influential with women. Language had no effect on how influential men were. In a second study, 120 Ss listened to an audiotape of identical persuasive messages presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
396
9
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 497 publications
(430 citation statements)
references
References 82 publications
19
396
9
6
Order By: Relevance
“…The socialization explanation predicts that the greatest gender differences would be observed in the use of language in same gender interactions, because both parties would follow the same behavioral norms. In contrast, the social context explanation predicts that gender differences in language use would be greatest in opposite gender interactions, because gender becomes a status characteristic in opposite gender interactions (Carli, 1989(Carli, , 1990Leman, Ahmed, & Ozarow, 2005;Leman, Macedo, Bluschke, Hudson, Rawling, & Wright, 2011, Leaper, 2014.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The socialization explanation predicts that the greatest gender differences would be observed in the use of language in same gender interactions, because both parties would follow the same behavioral norms. In contrast, the social context explanation predicts that gender differences in language use would be greatest in opposite gender interactions, because gender becomes a status characteristic in opposite gender interactions (Carli, 1989(Carli, , 1990Leman, Ahmed, & Ozarow, 2005;Leman, Macedo, Bluschke, Hudson, Rawling, & Wright, 2011, Leaper, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Males may dominate social interactions through the use of more assertive language, whereas women may be more likely to act subordinately through using more affiliative language. This explanation would predict fewer differences between males and females in same-gender interactions because it is within opposite-gender interactions that gender becomes a status characteristic (Carli, 1989(Carli, , 1990Leman, Ahmed, & Ozarow, 2005;Leman, Macedo, Bluschke, Hudson, Rawling, & Wright, 2011, Leaper, 2014. Another important contextual factor is group size and familiarity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same vein, 15 Catalyst (1993) showed that CEOs were reluctant to appoint women as directors of BDs because they believe that females are unqualified. Carli (1990) and Heilman and Haynes (2005) documented that in a male-dominated context, female with work experience can neutralize negative opinions about women's performance, but they are presumed to be less competent than men. Thus, women begin their careers with 20 less human capital than men and reap less compensation than men (Tharenou et al, 1994).…”
mentioning
confidence: 99%